Na^＋/K^＋-ATPase α-subunit in swimming crab Portunus trituberculatus： molecular cloning, characterization, and expression under low salinity stress - 韩晓琳 刘萍 高保全 王好锋 段亚飞 徐文斐 陈萍 (Chinese journal of oceanology and limnology, 2015)
Na^＋/K^＋-ATPases are membrane-associated enzymes responsible for the active transport of Na^＋ and K^＋ ions across cell membranes, generating chemical and electrical gradients. These enzymes＇ α-subunit provides catalytic function, binding and hydrolyzing ATP, and itself becoming phosphorylated during the transport cycle. In this study, Na^＋/K^＋-ATPase α-subunit eDNA was cloned from gill tissue of the swimming crab Portunus trituberculatus by reverse-transcription polymerase chain reaction （RT-PCR） and rapid amplification of eDNA end methods. Analysis of the nucleotide sequence revealed that the eDNA had a full-length of 3 833 base pairs （bp）, with an open reading frame of 3 120 bp, 5＇ untranslated region （UTR） of 317 bp, and 3＇ UTR of 396 bp. The sequence encoded a 1 039 amino acid protein with a predicted molecular weight of 115.57 kDa and with estimated pI of 5.21. It was predicted here to possess all expected features of Na^＋/K^＋-ATPase members, including eight transmembrane domains, putative ATP-binding site, and phosphorylation site. Comparison of arnino acid sequences showed that the P. tritubereulatus α-subunit possessed an overall identity of 75%-99% to that of other organisms. Phylogenetic analysis revealed that this α-subunit was in the same category as those of crustaceans. Quantitative real-time RT-PCR analysis indicated that this α-subunit＇s transcript were most highly expressed in gill and lowest in muscle. RT-PCR analysis also revealed that α-subunit expression in crab gill decreased after 2 and 6 h, but increased after 12, 24, 48, and 72 h. In addition, α-subunit expression in hepatopancreas of crab decreased after 2-72 h. These facts indicated that the crab＇s Na^＋/K^＋-ATPase α-subunit was potentially involved in the observed acute response to low salinity stress.